Optonometric scales: history and optical principles - Rosane Arruda Dantas; Lorita Marlena Freitag Pagliuca (Rev Rene)
Optometric scale is one of the means of visual acuity detection. The present study aims to demonstrate aspects of the historical process as well as of the construction of such scales. The historical focus le. is based on the Snell and Descartes’ refraction law. The principles of the tables can be shown through Snellen scale with focus on the optotype position through line, in the interval and number of optotypes on the same line and among several lines; in the contrast: in angular progression, in the size of the optotype according to the visual coeffi cient and in the range of visual acuity resolution. It is important to remember that such items involve the basic matters and that there are those which are specifi c for certain tables. Knowing these principles makes it is easier to understand those of other scales and be able to choose the option that best fi ts the examiners’ objectives as well as clients’ needs.